Voltammetric determination of dopamine mediated by nanoparticle WO3/MWCNT modified glassy carbon electrode - Lim, Alvin Teik Zheng; Ando, Yoshito; Zawawi, Ruzniza Mohd (Research India Publications, 2017)
Chemically-modified electrode fabricated by mechanical attachment of multi-walled carbon nanotubes/tungsten oxide (MWCNTs/WO3) in the electrocatalytic study of dopamine was investigated. The MWCNTs/WO3 nanocomposite has been characterized using voltammetric techniques of cyclic voltammetry, chronoamperometry and chronocoulometry. The CNT/WO3/GCE induces a 2.9 enhancement oxidative peak with peak separation of approximately 200 mV, shifting towards a lower potential in the electrochemical oxidation of 0.4 mM dopamine at pH 7.0, in comparison with the WO3/GCE, MWCNTs/GCE and bare GCE. The lowering positive potential and enhancement current are evident of electrocatalysis process. From the calibration plot, the high sensitivity response of 57.00 μA/μM for the anodic peak with the detection limit of 0.018 μM (100 mV/s scan rate) of dopamine at the CNT/WO3/GCE were obtained. Based on the chronocoulometric study on 0.4 mM dopamine in 0.1 M KCl, the diffusion coefficient was found to be 5.43 x 10-8 cm2/s with the surface charge of 6.86 x 10-4 C/cm2. The easily prepared nanocomposite-modified electrode showed to have high sensitivity, selectivity and good reproducibility.